Effects of training in minimalist shoes on the intrinsic and extrinsic foot muscle volume - Chen, T. L.-W.; Sze, L. K. Y.; Davis, I. S.; Cheung, R. T. H. (Clinical Biomechanics, 2016)
Minimalist shoes have gained popularity recently because it is speculated to strengthen the foot muscles and foot arches, which may help to resist injuries. However, previous studies provided limited evidence supporting the link between changes in muscle size and footwear transition. Therefore, this study sought to examine the effects of minimalist shoes on the intrinsic and extrinsic foot muscle volume in habitual shod runners. The relationship between participants' compliance with the minimalist shoes and changes in muscle õvolume was also evaluated.